Acute Leukaemia following Dengue Infection in Nepalese Patients: A Report of Two Cases - Anushka Agrawal; Pratik Lamichhane; Rituraj Baral; Sabin Thapaliya (Case Reports in Hematology)
Dengue is a mosquito-borne, acute febrile illness caused by dengue viruses. The association between hematological malignancies and dengue infection is obscure, and the literature on this occurrence is also limited. We report two cases of acute leukaemia following dengue infection in a recent outbreak in Nepal. Our case reports suggest a possible association of acute leukaemia with dengue infection. The relationship should be explored further with observational studies.